Improving health perception through a transition care model for adolescents with congenital heart disease. Issue 4 (April 2019) - Flocco, Serena Francesca; Dellafiore, Federica; Caruso, Rosario; Giamberti, Alessandro; Micheletti, Angelo; Negura, Diana Gabriela; Piazza, Luciane; Carminati, Mario; Chessa, Massimo
Abstract : Aims: The aim of this study was to assess the impact of a transition clinic model on adolescent congenital heart disease (CHD) patients' health perception outcomes. The transition clinic model consists of multidisciplinary standardized interventions to educate and support CHD patients and represents a key element in the adequate delivery of care to these individuals during their transition from childhood to adulthood. Currently, empirical data regarding the impact of transition clinic models on the improvement of health perceptions in CHD adolescent patients are lacking. Methods: A quasi-experimental design was employed. Quality of life, satisfaction, health perceptions and knowledge were assessed at the time of enrolment (T0) and a year after enrolment (T1), respectively. During the follow-up period, the patients enrolled (aged 11–18 years) were involved in the CHD-specific transition clinic model (CHD-TC). Results: A sample of 224 CHD adolescents was enrolled (60.7% boys; mean age: 14.84 ± 1.78 years). According to Warnes' classification, 22% of patients had simple heart defect, 56% showed moderate complexity and 22% demonstrated severe complexity. The overall results suggested a good impact of the CHD-TC on adolescents' outcomes, detailing in T1 the occurrence of a reduction of pain ( P < 0.001) and anxiety ( P < 0.001) and an improvement of knowledge ( P < 0.001), life satisfaction ( P < 0.001), perception of health status ( P < 0.001) and quality of life ( P < 0.001). Conclusion: The CHD-TC seems to provide high-quality care to the patient by way of a multidisciplinary team. The results of the present study are encouraging and confirm the need to create multidisciplinary standardized interventions in order to educate and support the delivery of care for CHD adolescents and their families.